A Current Review of Foot Disorder and Plantar Pressure Alternation in the Elderly. Issue 1 (2nd September 2020) - Zhang, Bo; Lu, Qianyu
Fall is a very common injury, especially in older adults with foot deformities and other foot disorders. Even a small fall may cause fatal damage to this cohort. The purpose of this study was to conduct a review elucidating plantar pressure pattern under different foot deformities in the elderly. English-language search of the electronic databases in PubMed, ScienceDirect, Google Scholar, and Web of Science was conducted from 2000 to May 2020. Fifteen studies were found after literature searching and screening. Among them, 2 studies described the plantar pressure of plantar hyperkeratosis lesions in the elderly, 2 studies depicted the plantar pressure of pronated foot supinated foot in the elderly, 4 studies explored the plantar pressure distribution of hallux valgus and other foot deformities, and 7 studies focused on the plantar pressure of diabetic foot deformity in the elderly. Foot deformity appears to alter the plantar pressure in the elderly, and plantar pressure characteristics differ according to foot deformities.